Safety Profile of the Merck Human Immunodeficiency Virus-1 Clade B gag DNA Plasmid Vaccine With and Without Adjuvants. (17th May 2014) - Quirk, Erin K.; Brown, Elizabeth L.; Leavitt, Randi Y.; Mogg, Robin; Mehrotra, Devan V.; Evans, Robert K.; DiNubile, Mark J.; Robertson, Michael N.
Abstract: The immunogenicity results from 3 phase I trials of the Merck DNA human immunodeficiency virus (HIV) vaccine have previously been reported. Because preventive DNA vaccine strategies continue to be leveraged for diverse infections, the safety and tolerability results from these studies can inform the field moving forward, particularly regarding adverse reactions and adjuvants. No serious vaccine-related adverse events were reported during the 3-dose priming phase. Pain at the injection site was more common with adjuvanted formulations than with the phosphate-buffered saline diluent alone. Febrile reactions were usually low grade. Although the AlPO4 or CRL1005 adjuvants used in these studies did not significantly enhance the immunogenicity of the DNA vaccine, adverse events were numerically more common with adjuvanted formulations than without adjuvants.